Thai Burnout Assessment Tool (T-BAT): Translation, validity, and reliability testing in nurses - Posai, Vachira; Srisintorn, Wisarut; Thongsuksai, Paramee; Jitpanya, Chanokporn (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: The Burnout Assessment Tool (BAT), an instrument for measuring burnout among healthcare professionals, was originally developed in English and remains unadopted and unvalidated within the Thai healthcare context. Despite its widespread international use, cultural and linguistic variations necessitate rigorous contextual validation. Objective: This study aimed to translate the BAT into Thai (T-BAT) and evaluate its psychometric properties among Thai nurses, addressing critical gaps in cross-cultural burnout assessment. Methods: A cross-sectional survey was conducted among 1,005 nurses from two government hospitals in Thailand, employing a multistage sampling with quota-based convenience selection. Participant inclusion criteria comprised full-time nursing employment, a minimum bachelor’s degree in nursing, and at least three months of hospital work experience. The BAT underwent a back-translation process to ensure linguistic and cultural equivalence. The psychometric evaluation encompassed descriptive statistical analysis, internal consistency assessment, known-group validity testing through hypothesis, and construct validation via confirmatory factor analysis (CFA). Finally, Rasch analysis, evaluating item performance and measurement precision, was used. Results: The T-BAT exhibited robust psychometric characteristics, including internal consistency (Cronbach’s alpha = 0.93), known-group validity (significant score variations across nurse subgroups), and construct validity (confirmatory factor analysis validating the proposed four-factor model). Finally, Rasch analysis demonstrated optimal item performance, including fit statistics within acceptable ranges (Infit: 0.78-1.40; Outfit: 0.73-1.41). Person and item reliability indices consistently exceeded 0.80, indicating high reliability of the scale. Conclusion: The study substantiates the T-BAT as a reliable and valid instrument for assessing burnout among Thai nurses. This culturally adapted tool provides a context-specific approach to understanding burnout, potentially enabling more targeted interventions by healthcare policymakers, hospital administrators, and nursing leaders.